Ekoteologi sebagai Paradigma Baru Pengembangan Materi Pembelajaran Bahasa Arab di Indonesia - Muh. Sabilar Rosyad (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2026)
Environmental degradation has become a pressing global challenge, underscoring the need for educational approaches that integrate ecological responsibility with moral and spiritual values. Although Arabic language education in Indonesia has advanced through curricular and pedagogical innovations, the integration of Islamic ecotheology into Arabic teaching materials remains conceptually limited. This study aims to develop an ecotheology-based conceptual framework that integrates linguistic competence with environmental sustainability. Using qualitative library research and a conceptual paper approach, the study examined literature on Islamic ecotheology, Arabic language education, Education for Sustainable Development, and relevant Indonesian educational policies through content and descriptive-critical analyses. The findings demonstrate that the principles of khalifah, amanah, mizan, and islah provide a robust foundation for reconstructing Arabic teaching materials. The proposed framework reorients learning objectives, instructional content, and activities across the four language skills to simultaneously promote language proficiency, ecological literacy, and Islamic ethical values. It positions Arabic language learning as a medium for environmental awareness and value transformation while supporting national ecotheology initiatives and sustainable education. This study offers a novel conceptual paradigm linking Islamic ecotheology, Arabic language education, and sustainability, providing theoretical and practical guidance for developing transformative Arabic teaching materials in Indonesia.